2022
DOI: 10.1002/adma.202110343
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Memristor Based on Epitaxial Vertically Aligned Nanostructured BaTiO3−CeO2 Films on Silicon

Abstract: With the exploration of ferroelectric materials, researchers have a strong desire to explore the next generation of non‐volatile ferroelectric memory with silicon‐based epitaxy, high‐density storage, and algebraic operations. Herein, a silicon‐based memristor with an epitaxial vertically aligned nanostructures BaTiO3–CeO2 film based on La0.67Sr0.33MnO3/SrTiO3/Si substrate is reported. The ferroelectric polarization reversal is optimized through the continuous exploring of growth temperature, and the epitaxial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…As shown in Figure d, it can be observed that there is almost no fluctuation during 10 consecutive cycles, proving a superior stability. In addition, two kinds of short-term synaptic plasticity, PPF and PPD, which play a key role in the realization of advanced learning and memory in the human brain, were emulated in the Al/ZnO NPs/CuO NWs/Cu-based memristor. Thereinto, the PPF behavior was induced by the excitatory postsynaptic potential, while the PPD can be ascribed to the inhibitory postsynaptic potential.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure d, it can be observed that there is almost no fluctuation during 10 consecutive cycles, proving a superior stability. In addition, two kinds of short-term synaptic plasticity, PPF and PPD, which play a key role in the realization of advanced learning and memory in the human brain, were emulated in the Al/ZnO NPs/CuO NWs/Cu-based memristor. Thereinto, the PPF behavior was induced by the excitatory postsynaptic potential, while the PPD can be ascribed to the inhibitory postsynaptic potential.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decades, ferroelectric memory has been widely studied because of its fast-switching speed, good cycle durability, and simple physical mechanism. [155][156][157][158][159] Importantly, the storage mechanism of ferroelectric memory is generated by electrically switchable ferroelectric polarization, in which two ferroelectric polarization states corresponding to storage "0" and "1" are generated by positive and negative remanent polarizations. It is non-volatile [160] and the read/write process can be achieved up to nanosecond.…”
Section: Flexible Ferroelectric Memorymentioning
confidence: 99%
“…It is reasonable to deduce that the distribution of CeO 2 destroys the long‐range Coulomb potential of crystal and contributes to increased stability in this epitaxial film. [ 43 ]…”
Section: Fundamentals Of Ferroelectricitymentioning
confidence: 99%
“…It is reasonable to deduce that the distribution of CeO 2 destroys the longrange Coulomb potential of crystal and contributes to increased stability in this epitaxial film. [43] Besides organic polymers like PVDF and P(VDF-TrFE), many thin-film ferroelectrics have been applied in 2D devices. For instance, complex oxides ABO 3 -type perovskites and binary oxide HfO 2 with fluorite-structure are also used in the integration of ferroelectrics into 2D material-based devices.…”
Section: Ferroelectric Copolymer P(vdf-trfe) Filmsmentioning
confidence: 99%